TEACHERS’ PERCEPTION ON VOCABULARY TEACHING TECHNIQUES AT SMAN 14 SIGI - Muthmainnah Muthmainnah; Nadrun Nadrun; Anjar Dewi (Tadulako University, 2022)
The aim of this research is to find out the techniques used by the teachers in teaching vocabulary at SMA Negeri 14 Sigi and to find the students’ responses toward the teachers’ tecniques in teaching vocabulary at SMA Negeri 14 Sigi. This study employed descriptive qualitative research. The research instruments used to collect the data were interview and questionnaire. The findings show that there are two English teachers in SMA Negeri 14 Sigi, the first teacher (Y) used three techniques in teaching vocabulary: jumble word, making a match and games. Meanwhile the second teacher (E) used two techniques in teaching vocabulary: using picture and using video. The teacher used those techniques to improve students’ vocabulary mastery. The teacher can give the material clearly to the students by using those techniques. Based on the questionnaire, mostly the students were interested in learning by used that techniques. so can be seen if they enjoy the teaching learning process of English. The implication of this findings is the teacher needs to use other techniques that is interesting in teaching learning process and also use the other media to support teaching learning process.